Cyclic voltammetry of N-acetylated and N-quaternized monoazacrown ether substituted lutetium bis(phthalocyanines) - (:unkn) unknown (ROYAL SOC CHEMISTRY, 1995)
Cyclic voltammetry of N-quaternized (1) and N-acetylated (2) monoazocrown ether substituted monoprotonated lutetium bis(phthalocyanines) has been investigated on Pt as aqueous and/or dimethyl sulfoxide solutions.
Keywords: WATER; PHTHALOCYANINES; DERIVATIVES